Explanation:
1a) CaCO₃(s) → Ca²⁺(aq) + CO₃²⁻(aq)
1b) Remember, solids are not included in the equilibrium equation.
K = [Ca²⁺] [CO₃²⁻]
1c) Adding CO₃²⁻ ions will shift the reaction to the left, producing CaCO₃(s) until equilibrium is restored.
2) 2 SO₂(g) + O₂(g) → 2 SO₃(g)
Kc = 2.5×10¹⁰ = [SO₃]² / ([SO₂]² [O₂])
2a) SO₂(g) + ½ O₂(g) → SO₃(g)
Kc = [SO₃] / ([SO₂] [O₂]^½)
Kc² = [SO₃]² / ([SO₂]² [O₂])
Kc² = 2.5×10¹⁰
Kc ≈ 1.58×10⁵
2b) SO₃(g) → SO₂(g) + ½ O₂(g)
Kc = [SO₂] [O₂]^½ / [SO₃]
Kc = 1 / (1.58×10⁵)
Kc ≈ 6.33×10⁻⁶
2c) 3 SO₂(g) + ³/₂ O₂(g) → 3 SO₃(g)
Kc = [SO₃]³ / ([SO₂]³ [O₂]^³/₂)
Kc = ([SO₃] / ([SO₂] [O₂]^½))³
Kc = (1.58×10⁵)³
Kc ≈ 3.95×10¹⁵
3) H₂(g) + I₂(g) → 2 HI(g)
K = [HI]² / ([H₂] [I₂])
Make an ICE table.
[tex]\left[\begin{array}{cccc}&Initial&Change&Equilibrium\\H_{2}&0.400&-0.240&0.160\\I_{2}&1.60&-0.240&1.360\\HI&0&+0.480&0.480\end{array}\right][/tex]
K = (0.480)² / (0.160 × 1.360)
K = 1.06